FACING ASEAN ECONOMY COMMUNITY (AEC): DEVELOPING COMMUNICATIVE COMPETENCE FOR GOLF CADDY IN NEW KUTA GOLF, PECATU, BALI - Susanti, Luh Eka (International Journal of Linguistics and Discourse Analytics, 2019)
Indonesia has been a member of the Asean Economy Community (AEC) since 2016 and by becoming a member of the MEA, Indonesia has turned into a strategic market in marketing foreign products both goods and services. With the existence of the AEC, a single market will be created in the ASEAN region. This single market will create a free flow of goods, services, and capital and investment trade. In addition to getting a lot of benefits from it, there are also many challenges faced, one of which is in terms of the readiness of its human resources. Lack of skills to communicate with foreigners is one thing that needs to be highlighted. The same thing happened to the golf caddy at New Kuta Golf Pecatu who still uses body language to communicate with international tourists. This research aims to identify the needs analysis of the caddies to develop their communicative competence to have meaningful communication with the guests. English for Caddy is a form of English for Specific Purposes (ESP), in which the results of this research can be used as a reference for subsequent research, namely syllabus planning and the development of teaching materials of ESP. There were 20 caddies as the informants to be involved. The data collection was done through observations, questionnaire and interview.